The Remarkable Cationic Peptides: A Boon to Pharmaceutical Sciences? - Ruchi Omar; Arpita Yadav (Frontiers Media S.A., 2018)
In this opinion article, the authors discuss a number of interesting, beneficial properties of naturally occurring and synthetic cationic antimicrobial peptides (AMPs) with the prospective aim of bringing these compounds into therapeutic use to avoid antibiotic resistance and utilize their numerous properties. The structural diversity and the conformational freedom of these compounds adversely affects their mechanistic elucidation. Our molecular level mechanistic exploration of these peptides has shown their ion carriage properties and systematically explains their antibiotic activity through disruption of bacterial cell homeostasis and inhibition of 14-α demethylase enzyme. We have also shown self-assemblage in AMPs in different nanoparticulate and tubular forms. Some AMPs possess cell penetration capability and their co-administration with drug enhances antibacterial activity through a non-disruptive mechanism. The anti-HIV activity of AMPs has been explained based on their non-covalent, non-base-pair base-pair type interactions with HIV viral ssRNA template. Design of peptidomimetic compounds with enhanced druggability based on our mechanistic explorations will definitely lead to better non-toxic drugs with antibacterial, anti-HIV activity and may contribute towards development of efficient drug delivery systems.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.